Effect of chlorophyll biosynthesis-related genes on the leaf color in Hosta (Hosta plantaginea Aschers) and tobacco (Nicotiana tabacum L.) - Zhang, Jingying (BMC Plant Biol, 2021)
BACKGROUND: ‘Regal Splendour’ (Hosta variety) is famous for its multi-color leaves, which are useful resources for exploring chloroplast development and color changes. The expressions of chlorophyll biosynthesis-related genes (HrHEMA, HrPOR and HrCAO) in Hosta have been demonstrated to be associated with leaf color. Herein, we isolated, sequenced, and analyzed HrHEMA, HrPOR and HrCAO genes. Subcellular localization was also performed to determine the location of the corresponding enzymes. After plasmid construction, virus-induced gene silencing (VIGS) was carried out to reduce the expressions of those genes. In addition, HrHEMA-, HrPOR- and HrCAO-overexpressing tobacco plants were made to verify the genes function. Changes of transgenic tobacco were recorded under 2000 lx, 6000 lx and 10,000 lx light intensity. Additionally, the contents of enzyme 5-aminolevulinic acid (5-ALA), porphobilinogen (PBG), chlorophyll a and b (Chla and Chlb), carotenoid (Cxc), superoxide dismutase (SOD), peroxidase (POD), malondialdehyde (MDA), proline (Pro) and catalase (CAT) under different light intensities were evaluated. RESULTS: The silencing of HrHEMA, HrPOR and HrCAO genes can induce leaf yellowing and chloroplast structure changes in Hosta. Specifically, leaves of Hosta with HrCAO silencing were the most affected, while those with HrPOR silencing were the least affected. Moreover, all three genes in tobacco were highly expressed, whereas no expression was detected in wild-type (WT). However, the sensitivities of the three genes to different light intensities were different. The highest expression level of HrHEMA and HrPOR was detected under 10,000 lx of illumination, while HrCAO showed the highest expression level under 6000 lx. Lastly, the 5-ALA, Chla, Cxc, SOD, POD, MDA, Pro and CAT contents in different transgenic tobaccos changed significantly under different light intensities. CONCLUSION: The overexpression of these three genes in tobacco enhanced photosynthesis by accumulating chlorophyll content, but the influential level varied under different light intensities. Furthermore, HrHEMA-, HrPOR- and HrCAO- overexpressing in tobacco can enhance the antioxidant capacity of plants to cope with stress under higher light intensity. However, under lower light intensity, the antioxidant capacity was declined in HrHEMA-, HrPOR- and HrCAO- overexpressing tobaccos. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12870-020-02805-6.